86TH Annual Georgia Public Health Association Meeting & Conference Report - Selina Smith; Regina Abbott; Christy Sims (Georgia Southern University, 2015)
The 86th annual meeting of the Georgia Public Health Association (GPHA) and joint conference with the Southern Health Association was held in Atlanta, Georgia, on April 13-14, 2015, with pre-conference (April 12th) and post-conference (April14th) Executive Board meetings. As Georgia's leading forum for public health researchers, practitioners, and students, the annual meeting of the GPHA brings together participants from across the state to explore recent developments in the field and to exchange techniques, tools, and experiences. Historically, the GPHA conference has been held in Savannah (n=24); Jekyll Island (n=20); Atlanta (n=16); Augusta (n=4); and Gainesville (n=1). There was no annual meeting during the early years (1929-1936); during World War II (1941-1943 and 1945); and for four years during the 1980s. Between 2006 and 2010, GPHA held one-day annual meetings and business sessions with educational workshops. Several new initiatives were highlighted as part of this year's conference. These included a "move and groove" physical activity lounge, registration scholarships for students with a dedicated meet-and-greet reception, an expanded exhibit hall, presentation and approval of three resolutions (related to healthy foods at official activities and events; weapons at official activities and events; and memorials), and approval of the 2015 legislative policy positions and amended association bylaws. The theme for the conference was Advocacy in Action for Public Health. Specifically, the program addressed ensuring access to care; protecting funding for core programs, services, and infrastructure; eliminating health disparities; and addressing key public health issues important to the state of Georgia. One hundred and nine (109) abstracts were submitted for peer review; 36 were accepted for poster and 40 for workshop presentations. Four plenary sessions with keynote speakers covered the intersection between advocacy and policy, Georgia's response to the Ebola crisis, palliative care, and essentials of advocacy in action for public health. Concurrent workshops focused on Board of Health training, public health accreditation, capacity building, collaboration, patient-centered outcomes, synthetic cannabinoid use, the HIV care continuum, use of data for informed decision making, environmental threats, organizational development, epidemiology, policy, and regulation. Thirty-two (32) awards were presented, including Lawmaker of the Year Award to Governor Nathan and First Lady Sandra Deal for their active and engaged role in promoting public health in Georgia; and the Sellers-McCroan Award to Commissioner Brenda Fitzgerald, Georgia Department of Public Health (DPH) State Health Officer, for her leadership of the Georgia Ebola Response Team and leadership of the newly formed department. The conference attracted 569 registrants primarily through pre-registration (n=561) with limited onsite registration (n=8). For this year's conference, there was a significant increase in attendance (36%) and exhibitors (33%) relative to 2014. Of registrants reporting GPHA section participation, representation included: academic (5%); administration (10%); boards of health (13%); career development (15%); emergency preparedness (2%); epidemiology (5%); health education and promotion (2%); information technology (2%); maternal and child health (3%); medical/dental (3%); nursing (10%); nutrition (